Meningkatkan Keterampilan Penyelesaian Masalah Sosial Siswa Melalui Penerapan Model Pembelajaran Inkuiri di Kelas V SDN 091631 Pematang Kerasan - Prinawati Saragih; Lina Herlina (Departement of Mathematics Education, 2023)
Researchers are trying to apply the social inquiry learning model to improve social problem solving skills at SD Negeri 091631 Pematang Kerasaan. The hope is that by applying the social inquiry learning model it can improve students' skills in solving social problems. So that in the future a young generation will be created who is intelligent, tough, accomplished and useful for the family, community, nation and state. The aim of this classroom action research is to solve problems, improve conditions, develop and improve the quality of learning. The results of this research are that students' activities in participating in learning carried out by teachers using the social inquiry learning model show increased results. The aspect of student activity with the highest score lies in formulating problems, collecting evidence and facts, and concluding learning. Students' skills in solving social problems show increasing results. The aspect of students' skills with the highest score is developing resolution strategies and evaluating the results of solving social problems. Students' responses to the teacher's learning through the social inquiry learning model showed good results. The highest response was that students felt happy taking part in learning, felt happy expressing opinions, felt happy exploring social problems and determining solutions, and felt it was easy to understand the material.